GAMBARAN KEPATUHAN PENERAPAN PROTOKOL KESEHATAN IBU HAMIL PADA MASA ADAPTASI KEBIASAAN BARU DI PUSKESMAS 1 DENPASAR SELATAN - Wulandari, Putu Aditya Ika; Astuti, Ika Widi; Pramitaresthi, I Gusti Ayu; Sawitri, Ni Komang Ari (Coping: Community of Publishing in Nursing; Vol 12 No 2 (2024): April 2024DO - 10.24843/coping.2024.v12.i02.p13, 2024)
Entering a period of new normal, health protocols must still be applied to prevent infection, especially in pregnant women who are included in the vulnerable group. The implementation of the health protocol is an effort made by the government in preventing the transmission of COVID-19. This study aims to describe adherence to the implementation of health protocols for pregnant women during the new normal. The type of research used is quantitative descriptive research. The number of respondents in the study were 30 pregnant women who were selected by purposive sampling. The research instrument used was a compliance questionnaire that had been tested for validity and reliability. The results showed that the average age of the respondents was 26,5 years, the average gestational age of the respondents was 25,6 weeks, the majority of respondents were in gravida 1 (primipara) of 46,7%, the majority had high school/vocational high school education (53,3%), the majority of respondents did not work (63,3%). The results of the compliance questionnaire show that the majority of respondents are in the compliance category with the application of health protocols of 63,3%. One of the causes is that there are still pregnant women who don't even comply with health protocols due to a lack of knowledge and awareness of pregnant women in preventing Covid-19, so an appropriate strategy is needed to increase adherence in implementing health protocols, namely by disseminating information and educating pregnant women about the importance of complying health protocols to prevent the spread of the COVID-19 virus.